Analisis Perilaku Pengendara Kendaraan Roda Dua dan Impikasinya Terhadap Keselamatan Berkendara di Kota Balikpapan dengan Pendekatan Structural Equation Modeling - Lintang Nataniela Dewanti; Riki Herliansyah; Muqimuddin Muqimuddin; Abdul Alimul Karim (Universitas Islam Raden Rahmat, Malang, 2024)
The number of traffic accidents related to motorbikes in Balikpapan City increases every year, this is caused by motorbike riders committing traffic violations, so efforts are needed to implement safe driving behavior for motorbike riders. This research aims to determine the fit of the Structural Equation Modeling (SEM) model with the Partial Least Square (PLS) approach and determine the variables that have a significant influence in determining the influence of motorbike rider behavior on driving safety in Balikpapan City. This research uses primary data from 322 motorbike riders in Balikpapan City using the Structural Equation Modeling (SEM) method and Partial Least Square (PLS) approach which was processed using SmartPLS software. The results of the research show that the Structural Equation Modeling (SEM) model with the Partial Least Square approach is declared fit and there are two variables that have a significant influence, namely risk perception and aggressive behavior variables